Peginterferon lambda for the treatment of hospitalized patients with mild COVID-19: A pilot phase 2 randomized placebo-controlled trial - Kim, Myung-Ho; Elbaz, Josh; Jilg, Nikolaus; Gustafson, Jenna L.; Xu, Min; Hatipoglu, Dilara; Nohelty, Eric; Kim, Arthur Y.; Chung, Raymond T. (Frontiers in Medicine, 2023)
Background This study aimed to investigate the efficacy and safety of subcutaneous injection of peginterferon lambda in patients hospitalized with COVID-19. Methods In this study (NCT04343976), patients admitted to hospital with COVID-19 confirmed by RT-PCR from nasopharyngeal swab were randomly assigned within 48 h to receive peginterferon lambda or placebo in a 1:1 ratio. Participants were subcutaneously injected with a peginterferon lambda or saline placebo at baseline and day 7 and were followed up until day 14. Results We enrolled 14 participants; 6 participants (85.7%) in the peginterferon lambda group and 1 participant (14.3%) in the placebo group were treated with remdesivir prior to enrollment. Fifty percent of participants were SARS-CoV-2 RNA negative at baseline although they tested SARS-CoV-2 RNA positive within 48 h of randomization. Among participants who were SARS-CoV-2 positive at baseline, 2 out of 5 participants (40%) in the peginterferon lambda group became negative at day 14, while 0 out of 2 participants (0%) in the placebo group achieved negativity for SARS-CoV-2 by day 14 (p > 0.05). The median change in viral load (log copies per ml) was +1.72 (IQR −2.78 to 3.19) in the placebo group and −2.22 (IQR −3.24 to 0.55) in the peginterferon lambda group at day 14 (p = 0.24). Symptomatic changes did not differ between the two groups. Peginterferon lambda was well tolerated with a few treatment-related adverse effects. Conclusion Peginterferon lambda appears to accelerate SARS-CoV-2 viral load decline and improve plasma disease progression markers in hospitalized patients with COVID-19.